2021
DOI: 10.1007/s00404-020-05923-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of severe psychological stressors in women during fertility treatment: Japan-Female Employment and Mental health in Assisted reproductive technology (J-FEMA) study

Abstract: Purpose To identify risk factors for severe psychological stress in women undergoing fertility treatment. Methods This cross-sectional, multi-center study was conducted from August to December 2018. We recruited 1672 subjects who completed an anonymous, self-reported questionnaire regarding fertility treatment, conditions at work and home, and psychological stress using K6 score, which estimates psychological distress during the previous 30 days. We further focused our analysis on 1335 subjects who were workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Employment status had significant associations with various mental health conditions [ 47 , 48 , 53 , 58 60 ]. Employed women had lower anxiety, depression and stress levels [ 47 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Employment status had significant associations with various mental health conditions [ 47 , 48 , 53 , 58 60 ]. Employed women had lower anxiety, depression and stress levels [ 47 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Employed women had lower anxiety, depression and stress levels [ 47 , 60 ]. Conversely, perceived difficulties to continue working during fertility treatment and infertility-related harassment in the workplace were associated with higher rates of psychological distress [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst evidence is limited, the same can be seen elsewhere. A 2017 Japanese government survey (in Ikemoto et al, 2021) reported little ART-related provision, with just 6.2% of responding organisations offering leave, and 1.9% offering financial subsidy.…”
Section: The Meso-level: Art and Employmentmentioning
confidence: 99%
“…A 2018 survey found that 7.4% of women who underwent infertility treatment experienced harassment because of it 11) . Of the women who were working at the start of infertility treatment, 16.7-50.1%, or one in 2-6, had left the workforce 10,12,13) , with the lack of workplace support being one of the risk factors for leaving 10,13) . Thus, women are subjected to various occupational stressors owing to pregnancy and childbirth.…”
Section: Introductionmentioning
confidence: 99%